Implementation of an intensive adherence intervention in patients with second-line antiretroviral therapy failure in four west African countries with little access to genotypic resistance testing: a prospective cohort study. Issue 11 (November 2019) - Eholie, Serge P; Moh, Raoul; Benalycherif, Aïda; Gabillard, Delphine; Ello, Frédéric; Messou, Eugène; Zoungrana, Jacques; Diallo, Ismaël; Diallo, Mouhamadou; Bado, Guillaume; Cisse, Mamadou; Maiga, Almoustapha I; et al.
Summary: Background: The decision about whether to switch to third-line antiretroviral therapy (ART) in patients with treatment failure on second-line therapy is difficult in settings with little access to genotypic resistance testing. In this study, we used a standardised algorithm including a wide range of adherence-enhancing interventions followed by a new viral load measurement to decide whether to switch to third-line therapy in this situation. The decision, made on the basis of effectiveness of the adherence reinforcement to drive viral resuppression, did not use genotypic resistance testing. Methods: In this prospective cohort study, adults in four west African countries with treatment failure of a boosted protease inhibitor ART regimen were offered nine adherence reinforcement interventions, and followed up for 64 weeks. We measured viral load at week 12 and used the results to decide ART treatment at week 16: if successful resuppression (plasma HIV-1 RNA <400 copies per mL or had decreased by ≥2 log10 copies per mL compared with baseline), patients continued the same second-line regimen; otherwise they switched to a third-line regimen based on ritonavir-boosted darunavir and raltegravir. The primary endpoint was virological success at week 64 (plasma HIV-1 RNA <50 copies per mL). After study termination we did genotypic resistance testing on frozen plasma samples collected at baseline, and retrospectively determined the appropriateness of the week 16 decision on the basis of the baseline genotypic susceptibility score. Findings: Between March 28, 2013, and May 11, 2015, of the 198 eligible participants, five died before week 16. Of the 193 remaining, 130 (67%) reached viral resuppression and continued with second-line ART, and 63 (33%) switched to third-line ART at week 16. Post-study genotypic resistance testing showed that the baseline genotypic susceptibility score was calculable in 166 patients, of whom 57 (34%) had a score less than 2. We retrospectively concluded that the week 16 decision was appropriate in 145 (75%) patients. At week 64, four patients (2%) were lost to follow-up, ten (5%) had died, and 101 (52%) had a viral load less than 50 copies per mL. Interpretation: Poor adherence is the first problem to tackle in patients for whom second-line ART is failing when resistance tests are not routinely available and is effectively a manageable problem. Lack of access to genotypic resistance testing should not be an obstacle to the prescription of third-line ART in patients who do not achieve viral resuppression after adherence reinforcement. Funding: French Agency for Research on AIDS and Viral Hepatitis.